2021
DOI: 10.1002/smll.202007357
|View full text |Cite
|
Sign up to set email alerts
|

Arrayed MoS2–In0.53Ga0.47As van der Waals Heterostructure for High‐Speed and Broadband Detection from Visible to Shortwave‐Infrared Light

Abstract: A high‐speed and broadband 5 × 5 photodetector array based on MoS2/In0.53Ga0.47As heterojunction is successfully demonstrated to take full advantage of the type‐II band‐aligned multilayer MoS2/In0.53Ga0.47As. The fabricated devices exhibit good uniformity in the Raman spectrum and clear rectifying characteristics. The fabricated MoS2/In0.53Ga0.47As photodetectors show good optical performances at a broad wavelength range showing high responsivities corresponding to the detectivity of ≈1010 Jones at −3 V for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
(51 reference statements)
0
19
0
Order By: Relevance
“…[3][4][5][6] In particular, the metal-organic chemical vapor deposition (MOCVD) growth technique for 2D TMDCs has emerged as an industry-friendly process. [7][8][9][10][11][12] For the growth of 2D TMDCs, nucleation can be effectively suppressed by introducing alkali metal powders (e.g., NaCl and KCl) during the MOCVD process. [13][14][15][16][17][18][19] However, previous studies using alkali metal precursors have several drawbacks because the growth of TMDCs was performed by placing solid alkali metal precursors with low vapor pressure inside the growth chamber.…”
Section: Doi: 101002/smll202106368mentioning
confidence: 99%
“…[3][4][5][6] In particular, the metal-organic chemical vapor deposition (MOCVD) growth technique for 2D TMDCs has emerged as an industry-friendly process. [7][8][9][10][11][12] For the growth of 2D TMDCs, nucleation can be effectively suppressed by introducing alkali metal powders (e.g., NaCl and KCl) during the MOCVD process. [13][14][15][16][17][18][19] However, previous studies using alkali metal precursors have several drawbacks because the growth of TMDCs was performed by placing solid alkali metal precursors with low vapor pressure inside the growth chamber.…”
Section: Doi: 101002/smll202106368mentioning
confidence: 99%
“…It was found that detectivity was enhanced from 10 9 to 10 10 jones (1 jones = 1 cm Hz 1/2 W −1 ) with the increase in the reverse bias, which exhibits excellent performance as compared to the previously reported work. 84 These results indicated that the progression of MoS 2 /In 0.53 Ga 0.47 As heterostructures is one of the feasible approaches to expand future applications such as communications, imaging, and sensors.…”
Section: Two-dimensional Tmd-based Photodetectorsmentioning
confidence: 87%
“…The device showed excellent uniformity in the structure and clear electrical rectifying properties. 84 To fabricate the MoS 2 /In 0.53 Ga 0.47 As PDs, the multilayer MoS 2 films were blended on the p-type 500 nm-thick In 0.53 Ga 0.47 As epitaxial structure with Au (gold) electrodes through metal–organic chemical vapor deposition (MOCVD), as represented in Fig. 3(a).…”
Section: Two-dimensional Tmd-based Photodetectorsmentioning
confidence: 99%
“…In contrast to photodetectors (PDs) that only respond to a specific wavelength range, broadband photodetectors, which can detect from the ultraviolet (UV) to near-infrared (NIR) wavelengths, are very attractive in fields such as optical communications, , image sensing, , and daytime/night-time monitoring . Conventional commercial detectors based on III–V compound semiconductors, such as those based on InGaAs and InGaAsP, are limited by the high cost of the technology and the difficulty of integration with readout circuits, which prevent them from being widely used .…”
Section: Introductionmentioning
confidence: 99%